2022
DOI: 10.1159/000524166
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-Metabolic Factors Associated with Cognitive Impairment in Chronic Kidney Disease: A Pilot Study

Abstract: <b><i>Introduction:</i></b> The associations of kidney-metabolic biomarkers with cognitive impairment (CI) beyond the estimated glomerular filtration rate (eGFR, in mL/min/1.73 m<sup>2</sup>) and albuminuria levels are not well understood. In exploratory analysis, our objective was to determine the extent that three kidney-metabolic factors, previously proposed as mechanisms of CI and commonly abnormal in chronic kidney disease (CKD), were associated with prevalent CI in CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…The study sample found a significant positive correlation between CKD and CoI. This finding is consistent with a previously reported prospective study that observed a correlation between declining kidney function and CoI, even in patients with mild CKD [ 36 ]. Another large-scale national study in the United States revealed that CKD is associated with an increased prevalence of CoI, which rises by 11% for every 10 mL/min/1.73 m 2 (< 60 mL/min/1.73 m 2 ) decrease in eGFR [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The study sample found a significant positive correlation between CKD and CoI. This finding is consistent with a previously reported prospective study that observed a correlation between declining kidney function and CoI, even in patients with mild CKD [ 36 ]. Another large-scale national study in the United States revealed that CKD is associated with an increased prevalence of CoI, which rises by 11% for every 10 mL/min/1.73 m 2 (< 60 mL/min/1.73 m 2 ) decrease in eGFR [ 37 ].…”
Section: Discussionsupporting
confidence: 92%